2014
DOI: 10.18195/issn.0313-122x.78(2).2014.443-483
|View full text |Cite
|
Sign up to set email alerts
|

Pilbara stygofauna: deep groundwater of an arid landscape contains globally significant radiation of biodiversity

Abstract: -The Pilbara region was surveyed for stygofauna between 2002 and 2005 with the aims of setting nature conservation priorities in relation to stygofauna, improving the understanding of factors affecting invertebrate stygofauna distribution and sampling yields, and providing a framework for assessing stygofauna species and community signifi cance in the environmental impact assessment process.Approximately 350 species of stygofauna were collected during the survey and extrapolation suggests that 500-550 actually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 70 publications
(109 reference statements)
2
38
0
Order By: Relevance
“…While the main purpose of this paper is to highlight the value of scraping as a technique for collecting troglofauna from the vadose zone, the results of the sampling reported here also show that the Pilbara region of Western Australia supports a significant troglofauna community and complements the results of other subterranean surveys showing the Pilbara is rich in stygofauna (Eberhard et al 2009, Halse et al 2014. Sampling of 59 mostly small areas in the Pilbara collected 549 species and morphospecies considered to be troglofauna.…”
Section: Richness Of Troglofauna In Pilbarasupporting
confidence: 58%
“…While the main purpose of this paper is to highlight the value of scraping as a technique for collecting troglofauna from the vadose zone, the results of the sampling reported here also show that the Pilbara region of Western Australia supports a significant troglofauna community and complements the results of other subterranean surveys showing the Pilbara is rich in stygofauna (Eberhard et al 2009, Halse et al 2014. Sampling of 59 mostly small areas in the Pilbara collected 549 species and morphospecies considered to be troglofauna.…”
Section: Richness Of Troglofauna In Pilbarasupporting
confidence: 58%
“…17%, 12% cf. 16% respectively; Eberhard et al 2005) and copepod proportions comparable to experiences in eastern Australia and the Pilbara (Eberhard et al 2005, Halse et al 2014). However, Queensland stygofauna communities differ due to the dominance of oligochaetes (16% cf.…”
Section: Global and Local Significance Of Queensland Faunamentioning
confidence: 59%
“…Western Australia) provide the most appropriate baseline for comparison given the higher survey effort employed in these regions , Halse et al 2014. While research has identified that eastern Queensland supports moderate richness stygofauna communities , Cook et al 2012, Halse et al 2014, our analysis highlights that this estimate is too low due to the low sampling effort and limited sampling coverage that largely excludes arid regions and low taxonomic resolution.…”
Section: Global and Local Significance Of Queensland Faunamentioning
confidence: 78%
See 2 more Smart Citations